Kompleksitas Kalimat pada Anak Usia 12 Tahun: Kajian Perkembangan Sintaksis - Rachel Camila Rachim; Hesti Hesti; Dona Aji Karunia Putra (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Language development in a child is related to the cognitive development that the child has mastered. This research aims to describe the extent of language development in 12 year old children in expressing opinions. This research method uses a descriptive qualitative approach. The subject in this study was a 12 year old child, male, and with the initials AMF. This data comes from interactive interview tests and listening and note-taking techniques regarding AMF's opinions. The results of the research show that: (1) the language development of a 12 year old boy with the initials AMF is perfect. (2) AMF has mastered the syntactic aspects and found 2 sentence structures, namely simple sentence structures and complex sentence structures. (3) in the interview results, AMF can speak sentences well and complexly.